A Critical Analysis of Zimbabwe’s Mines and Minerals Bill in Relation to Strategic Minerals - Victor Kudakwashe Mapuvire; Ricky Munyaradzi Mukonza (Universitas Negeri Semarang, 2025)
This paper critically analyses Zimbabwe’s Mines and Minerals Amendment Bill (MMAB), which seeks to reform the outdated Mines and Minerals Act [Chapter 21:05] of 1961. While the Bill introduces progressive elements, particularly through the formal designation of strategic minerals vital to the country’s economic, industrial, social, and security interests, it falls short in several key areas. The MMAB identifies minerals such as lithium, uranium, rare earth elements, and copper as strategic, and mandates that both the State and local communities hold defined stakes in their exploitation. However, the exclusion of critical minerals like gold, iron, chromium, and platinum group metals raises concerns about inconsistencies in mineral prioritisation. The paper highlights deficiencies in the Bill’s failure to clearly define the “special and unique conditions” applied to strategic minerals, as well as its lack of transparent guidelines for their designation—both of which undermine investor confidence and violate international best practices. Furthermore, the MMAB centralises decision-making power within the Ministry of Mines and the Presidency, creating excessive bureaucratic overlap and enabling potential political interference. The Bill also lacks clear frameworks for contract transparency, parliamentary oversight, community benefit-sharing, competitive bidding, and decentralisation of mining governance. To address these shortcomings, the paper recommends that the MMAB be reformed to align with Zimbabwe’s Constitution and international standards such as the Africa Mining Vision and Extractive Industries Transparency Initiative (EITI). A decentralised, inclusive, and transparent legal framework is essential for transforming Zimbabwe’s mining sector into an engine of broad-based economic growth and social development.